Evidence-Based Medicine: Present Status and Future Directions - Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2025)
Evidence-based medicine (EBM) emphasizes the systematic and judicious use of the best available evidence in clinical decision-making aligning treatment options with individual patients’ values and circumstances. It integrates clinical expertise, patient preferences, and research evidence to optimize patient care.  By adopting EBM principles, clinicians improve care quality, ensure ethical decision-making, and adapt to the evolving landscape of medical science. This dynamic paradigm advances patient outcomes while providing a compassionate and evidence-driven healthcare environment. However, challenges such as information overload, resource constraints, and variations in evidence quality necessitate continuous learning and systematic approaches. This article explores the historical evolution of EBM, its foundational principles, and the structured five-step process: Assess, Ask, Acquire, Appraise, and Apply.